2017
DOI: 10.1007/s00394-017-1562-4
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional investigation into the occupational and socio-demographic characteristics of British police force employees reporting a dietary pattern associated with cardiometabolic risk: findings from the Airwave Health Monitoring Study

Abstract: PurposeThe aims of this study were to (1) determine the association between diet quality using the Dietary Approaches to Stop Hypertension (DASH) score and cardiometabolic risk in a British working population and (2) identify employee characteristics associated with reporting a poorer quality dietary pattern.MethodsBritish police employees enrolled (2007–2012) into the Airwave Health Monitoring Study (n = 5527) were included for sex-specific cross-sectional analyses. Dietary intakes were measured using 7-day f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…Furthermore, a frequently overlooked aspect of working hour research is the co-existence of long working hours and shift work (H€ arm€ a et al 2015). This association has been observed in British police employees (Gibson et al 2017); however, the significance of this in relation to dietary intake is yet to be investigated. To draw causal inference from observational findings requires biological plausibility.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Furthermore, a frequently overlooked aspect of working hour research is the co-existence of long working hours and shift work (H€ arm€ a et al 2015). This association has been observed in British police employees (Gibson et al 2017); however, the significance of this in relation to dietary intake is yet to be investigated. To draw causal inference from observational findings requires biological plausibility.…”
Section: Discussionmentioning
confidence: 86%
“…This association has been observed in British police employees (Gibson et al . ); however, the significance of this in relation to dietary intake is yet to be investigated. To draw causal inference from observational findings requires biological plausibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…b Metabolic syndrome was diagnosed based on the presence of three of the five risk criteria from the joint statement by the International Diabetes Federation; American Heart Association; National Heart, Lung, and Blood Institute; World Heart Federation, International Atherosclerosis Society; and International Association for the Study of Obesity. 10 ous studies have shown that long working hours are associated with poor diet quality, 31 smoking, 32 and physical inactivity. 33 Because transportation workers likely work prolonged hours, it may be difficult for them to maintain healthy lifestyle habits.…”
Section: Discussionmentioning
confidence: 99%